Provisions against wealth and poverty in Plato"s Cretan city and in ancient Israel: A comparison of the Book of Deuteronomy with Plato"s Nomoi - Otto, Eckart (HTS teologiese studies, 2019)
The way in which a nation’s economy is structured is of great importance for the material welfare of its people as well as the people’s relationship with the state and the operation of the state itself. It is also important for the proper functioning of a nation as a people and its psychological welfare. If the gap between rich and poor increases, the structure of an economy, and therefore the welfare of the state and the nation, is at risk. Two important documents of antiquity, Plato’s Nomoi and the Book of Deuteronomy, which even today influence life, dealt intensively with the fissures between rich and poor within society as a danger to political welfare and harmony. This article will examine these documents to make use of these two books for improving a societal situation. This will be done by a comparative perspective on both of these books.